Arabic for specific purpose: a compact language guide for pilgrimage and Umrah purposes (travelers) - Sahrir, Muhammad Sabri; Mohamed Gameil Ali, Hussein; Muhammad, Ilyani Syiham (2011)

(untitled)
This compact 200-page Arabic language guide book is designed for the consumption of non-native tourists and travellers to the Middle East region in general, and specifically for Pilgrim and Umrah purposes. The design is based on educational principles of Teaching Arabic for Specific Purpose (TASP) and Teaching Arabic as Foreign Language (TAFL) based on Tarey (1998), Abd. Rahman (2007), Conner (2007), Md. Taha (1994), Merriam (2001) and Abd Halim (2005). The language contents have been reviewed by several English, Arabic and Malay subject matter experts (SME) based on suggestions by Tessmer (1993) and Richey & Klein (2007).